Inovasi Pembelajaran Kombinasi Model Project Based Learning Dan Project Penguatan Profil Pelajar Pancasila Berbasis Devotion Untuk Meningkatkan Kemampuan Kolaborasi, Komunikasi, Kreativitas Dan Berpikir Kritis Mahasiswa - Suardi Suardi (Jurnal Riset dan Inovasi Pembelajaran, 2024)
The main problem in this research is learning innovation in the lecture process that can improve students' collaborative, creativity, communication and critical thinking skills. The purpose of this research is to improve students' collaborative, creativity, communication and critical thinking skills through a combination of the project-based learning model and the devotion-based Pancasila student profile project. This research uses a mixed research method (mixed methods). Research informants, qualitative research using purposive sampling numbered 32 people, while the determination of the research sample used the total sampling technique of 32 respondents. The data collection techniques used are the dissemination of questionnaires, observations, interviews, and documentation. Qualitative data analysis is done through the stages of data reduction, data display and drawing conclusions, while quantitative data analysis uses questionnaire verification, questionnaire data tabulation and questionnaire data percentage. The validity of qualitative data uses source triangulation and method triangulation, while quantitative data is tested for reliability (accuracy) and validation (true). The results of the research show that the application of Project Based Learning model learning innovations and devotion-based Pancasila student profile projects in Media and Learning Technology subjects have improved students' collaboration, creativity, communication and critical thinking skills.